Testing for Volatility Co-movement in Bivariate Stochastic Volatility Models - Jinghui Chen; Masahito Kobayashi; Michael McAleer (Tinbergen Institute, 2017)
The paper considers the problem of volatility co-movement, namely as to whether two nancial returns have perfectly correlated common volatility process, in the framework of multivariate stochastic volatility models and proposes a test which checks the volatility co-movement. The proposed test is a stochastic volatility version of the co-movement test proposed by Engle and Susmel (1993), who investigated whether international equity markets have volatility co-movement using the framework of the ARCH model. In empirical analysis we found that volatility co-movement exists among closelylinked stock markets and that volatility co-movement of the exchange rate markets tends to be found when the overall volatility level is low, which is contrasting to the often-cited nding in the nancial contagion literature that nancial returns have co-movement in the level during the nancial crisis.
Keywords: C12; C58; G01; G11; 330; Lagrange multiplier test; Volatility co-movement; Stock markets; Exchange rate Markets; Financial crisis